Differential Impact of ALK Mutations in Neuroblastoma. (2021) - O'Donohue, Tara; Gulati, Nitya; Mauguen, Audrey; Kushner, Brian H.; Shukla, Neerav; Rodriguez-Sanchez, M. I.; Bouvier, Nancy; Roberts, Stephen; Basu, Ellen; Cheung, Nai-Kong; Modak, Shakeel
Abstract : PURPOSE: The tyrosine kinase receptor anaplastic lymphoma kinase (ALK) can be abnormally activated in neuroblastoma, and somatic ALK mutations occur in 6%-10% of patients. The differential clinical impact of these mutations has not been clearly elucidated. METHODS: Data on patients with neuroblastoma harboring ALK mutations were retrospectively analyzed. ALK sequencing was performed by whole-genome sequencing, hybrid-based capture of targeted exomes, or hotspot ALK mutation profiling. The differential impact of ALK mutation site on clinical characteristics, response to treatment, and survival was analyzed. In a subgroup of patients with locoregional neuroblastoma diagnosed after 2014, the impact of all ALK mutations was compared with wild-type ALK. RESULTS: Of 641 patients with neuroblastoma with ALK status analyzed on at least one tumor sample, 103 (16%) had tumors harboring ALK mutations. Mutations existed across all ages (birth to 67.8 years), stages (30% locoregional and 70% metastatic), and risk groups (20%, 11%, and 69% with low-, intermediate-, and high-risk disease, respectively). Mutation sites included F1174 (51%), R1275 (29%), R1245 (10%), and others (10%). Mutation site was not prognostic for progression-free survival or overall survival in the entire cohort, high-risk subgroup, or locoregional subgroup. Locoregional tumors with any ALK mutation were generally invasive: L2 by International Neuroblastoma Research Group staging in 30/31 patients with a 2-year progression-free survival (59%, 95% CI, 37.4 to 80.5) that was inferior to historical controls. This observation was corroborated in the post-2014 subgroup in which gross total resection was less likely for ALK -mutated tumors. CONCLUSION: Somatic ALK mutations are present across all stages and risk groups of neuroblastoma. No specific mutation carries differential prognostic significance. Locoregional neuroblastoma has an invasive phenotype when harboring somatic ALK mutations in this population.